A study of correlation between clinical, radiological and pathological diagnosis of appendicitis: a retrospective analytic study - R., Prabhu; C., Vijayakumar; K., Balagurunathan; M., Senthil Velan; R., Kalaiarasi; T., Swetha (International Surgery Journal, 2018)
Background: Acute appendicitis is the most common cause of acute abdominal pain in young adults requiring emergency surgery. Appendicectomy is the most frequently performed surgery. The diagnosis is often challenging and the decision to operate in an emergency setting is always debatable. A combination of clinical signs and symptoms with laboratory findings in many scoring systems are suggesting the probability of appendicitis and the possible subsequent management pathway. The aim was to evaluate accuracy of the clinical Alvarado scoring system, radiological finding and histopathological examination for the diagnosis of acute appendicitis. Methods: A retrospective study was conducted in the department of general surgery in a tertiary care centre in South India. Total of 237 patients with acute abdominal pain were included and evaluated with the clinical Alvarado scoring system, radiological finding with (USG/CT abdomen) and histopathological examination for the diagnosis of acute appendicitis. The data was collected and analyzed retrospectively. Results: Of the 237 patients, 164 patients were male (69.1%) and rest is female. The correlation of the Alvaroda score with histopathological findings in groups with score > 7 and ≤7 the correlation of Alvarado score and the ultrasound findings were comparable between the study groups. The sensitivity of ultrasound in diagnosing acute appendicitis in patients with Alvarado score >7 was 72.99%. The sensitivity of ultrasound in diagnosing acute appendicitis in patients with Alvarado score ≤7 was decreased to 27%. Conclusions: The diagnostic accuracy of clinical features is far better than radiological investigations in the diagnosis of acute appendicitis. Therefore, it is concluded that it is better to use radiological investigations only to confirm the diagnosis of acute appendicitis rather to diagnose it.